Pemikiran Cak Nun tentang Harmoni Budaya dan Teknologi dalam Ruang Keagamaan - Laelani, Rizki; Mukarom, Zaenal (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2025)
This article analyzes Emha Ainun Nadjib's (Cak Nun) thoughts on the relationship between religion, culture, and technology from the perspective of contemporary Islamic communication. Based on the YouTube video